Building Energy Optimization Tools and Their Applicability in Architectural Conceptual Design Stage. (November 2015) - Tian, Z.C.; Chen, W.Q.; Tang, P.; Wang, J.G.; Shi, X.
Abstract: There is an on-going trend of incorporating optimization techniques into design to achieve energy efficient buildings. These techniques are particularly productive if they are applied in the architectural conceptual design stage because early design decisions generally have a more profound impact on the final quality of buildings compared with decisions made later. In this paper, the concept of energy efficient design optimization techniques is explained, followed by a review of the existing techniques and tools. The emphasis is placed on classifying these techniques and analyzing their applicability in the conceptual design stage from a perspective of architects. The applicability in the conceptual design stage is assessed from four angles, namely data completeness, interoperability with architectural models, optimized parameters, and post-processing capability. The results show that none of the existing techniques is able to fully address the architect's needs in the conceptual design stage and therefore, further research and development are needed.